Biopolitics of migration: An assemblage approach - Wiertz, Thilo (2021)
Abstract: Critical research on migration, borders and camps has used the notion of biopolitics to interrogate how sovereign power or the state differentiate and govern the life of mobile populations. Yet despite its popularity, biopolitical theory is not without limitations, particularly when used as an analytic lens for empirical research. Many theorists of biopolitics are concerned with grand historical shifts and binary oppositions between life and death, inclusion and exclusion, bare life and political rights. Such binaries have been challenged by recent research that points to complex and nuanced differentiations of belonging and citizenship, to the ambiguity of power relations, and that prioritizes the agency and experience of individuals over structuralist conceptions of oppression. Against this background, I suggest that assemblage thinking and the works of Deleuze and Guattari offer terms and concepts that can be made useful to reconsider biopolitics as an analytic approach. Assemblage thinking challenges traditional oppositions between the individual and the collective, structure and agency, oppression and resistance and may thus be more sensitive to the complexity of power relations that integrate the life of migrants. In particular, I examine how revised conceptions of power, life, difference and population challenge the assumption of a central origin of power and an understanding of biopolitics as spatially or historically confined. By considering biopolitics as multiple and becoming, analysis can become more sensitive to the biopolitical experience of migrants, and to the formation of alternative collectives and subjectivities that challenge the violent biopolitics of contemporary migration regimes